The Hours Before the Hours: Books of Hours and Almanacs at the Redwood. - Crowley, Patrick (Etc.: The Magazine of the Redwood Library and Athenæum., 2018)
Keywords: dept.lib

John J. Slocum the Collector. - Crowley, Patrick (Etc.: The Magazine of the Redwood Library and Athenæum, 2018)
Keywords: dept.lib

10 Questions: Siobhan McGuiness - Aschenbach, Jamie Marie (Information Outlook, 2017)
Keywords: dept.lib

Negotiating Your Best Journal Deals Yet - Aschenbach, Jamie Marie (Information Outlook, 2017)
Keywords: dept.lib

Patents & Business Intelligence - Jansen, Amy; Berry, R. (2013)
Keywords: dept.lib

Patent & Trademark Connections: One Library’s Partnership with the USPTO in Providing Intellectual Property Resources and Services to the Public - Jansen, Amy (2013)
Keywords: dept.lib

Patents as Business Intelligence Tools - Jansen, Amy (Journal of the Patent and Trademark Research Association, 2014)
Keywords: dept.lib; peer-reviewed; ⛔ No DOI found

Will You Ever Change? - Valognes, Aurélie (Amazoncrossing, 2017)
Keywords: Domestic fiction; French; dept.lib; faculty_collection

Fighting the Current: The Rise of American Women's Swimming, 1870-1926 - Bier, Lisa (McFarland & Co., 2011)
"This book describes the origins of women's competitive swimming in the United States. Women faced many obstacles to safe swimming opportunities, including restrictive beliefs about physical abilities, access to safe clean water, bathing suits that did not allow for movement, and opposition from official sporting organizations. This book is a testament to how far female athletes have come"–Provided by publisher.
Keywords: Ederle; Gertrude; 1906-2003; Olympic Games (7th : 1920 : Antwerp; Belgium); Olympic Games (8th : 1924 : Paris; France); Swimming for women; History; History; Swimming; United States; dept.lib; faculty_collection

Doing more with more: Systems, services and emerging technologies - Thomas, L.C. (An Overview of the Changing Role of the Systems Librarian: Systemic Shifts, 2010)
Journal Abbreviation: An Overv. of the Chang. Role of the Syst. Libr.: Syst. Shifts
Keywords: Emerging technologies; dept.lib

Handheld libraries 101 using mobile technologies in the academic library - Kosturski, K.; Skornia, F (Computers in Libraries, 2011)
Keywords: dept.lib; ⛔ No DOI found

Trendspotting 2011 - Thomas, L.C. (Journal of Web Librarianship, 2011)
0 citations (Crossref) [2023-10-31]
Keywords: dept.lib

Creation of a gamefish occurrence dataset from public-focused informational newsletters - Hedreen, Rebecca; Grace, Sean (MarXiv, 2019)
Fish and wildlife agencies produce a bounty of information aimed at the public. Under the right circumstances, that information can be compiled into scientifically useful data to complement full scientific studies. This poster describes some preliminary results from a project to compile mentions of gamefish species, locations, and sizes throughout the Long Island Sound and surrounding waters from the Weekly Fishing Report (2006, 2008-2018) and the Trophy Fish Report (2009-2017), both produced by the Connecticut Dept. of Energy and Environmental Protection. The dataset consists of more than 20,000 entries from the reports collected weekly by DEEP employees from tackle shops and charter companies. The current portion of the analysis is to determine the characteristics of the dataset, such as entry types, species counts, and some general trends. Presented at the 2019 NEAFWA Conference in Groton, CT and the 2019 CSCU Faculty Research Conference at SCSU in New Haven, CT.
0 citations (Crossref) [2023-10-31] type: article
Keywords: Coastal fisheries; Connecticut; Data collections; Estuarine fisheries; Fish catch statistics; Game fish; Geographical coordinates; Geographical distribution; Life Sciences; Long Island Sound; Marine Biology; Sport fishing statistics; dept.bio; dept.lib

Feelings Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
It’s never too early to encourage children to talk about how they feel. This newest title in the Pull and …
Keywords: dept.lib

Who Lives Where? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Sliding panels of animals near and far make for a delightful and satisfying format for matching game fun! Each of …
Keywords: dept.lib

Construction Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Bumpy roads, rough wood beams, and smooth concrete—there’s so much to discover in this Touch and ExploreTM book that’s all …
Keywords: dept.lib

Super Mazes in Space! Translated by Wendeline Hardenberg - Méhée, Loïc (Twirl Books, 2019)
Ten incredible mazes combine with a space adventure to provide a stellar game book for every puzzle-solving kid! Comics artist …
Keywords: dept.lib

Cars Translated by Wendeline Hardenberg - Krasinski, Geraldine (Twirl Books, 2019)
Turn a wheel to see cars of yesteryear, slide a new car onto a car carrier, pull a tab to …
Keywords: dept.lib

Yoga Together! Translated by Wendeline Hardenberg - Jouanne, Elisabeth (Twirl Books, 2019)
Keywords: dept.lib

Body Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Big, sturdy tabs to push and pull make for great learning fun in this brand-new nonfiction series. Preschool children learn …
Keywords: dept.lib

Baby Animals Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Keywords: dept.lib

Pirates Translated by Wendeline Hardenberg - Adams, Ines (Twirl Books, 2019)
Heave ho! Set sail on a high-seas adventure with swashbuckling pirates in search of treasure in this new Magnetology™ title. …
Keywords: dept.lib

Savanna Animals Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Take a trek into the wild . . . • Hunting for food • Building homes • Keeping cool • …
Keywords: dept.lib

Astronauts Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Count down to an incredible voyage! • Learning to pilot a spacecraft • Getting used to being weightless • Going …
Keywords: dept.lib

Jungle Animals Translated by Wendeline Hardenberg - Mazas, Marie (Twirl Books, 2019)
The shaggy fur of a sloth, the scaly skin of an iguana, and the rough hide of a tapir—there’s so …
Keywords: dept.lib

Bathtime Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
Little Crocodile, Little Monkey, and all their friends can think of a lot more things they’d rather do than take …
Keywords: dept.lib

Ultimate Book of Planet Earth Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2019)
The internationally successful Ultimate Book series expands its scope to embrace-very appropriately-the whole world! The Ultimate Book of Planet Earth …
Keywords: dept.lib

Badadoom Badabump! Translated by Wendeline Hardenberg - Baou, Bartélémi (Twirl Books, 2019)
Inspiring imagination and encouraging hours of creative play, Badaboom Badabump! is an innovative play set that not only includes a …
Keywords: dept.lib

[Two Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Ozone Park Journal, 2010)
Keywords: dept.lib

Max Ernst Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Qarrtsiluni Online Literary Magazine, 2011)
Keywords: dept.lib

[Seven Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (The Dirty Goat, 2011)
Keywords: dept.lib

[Five Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (TWO LINES Online, 2012)
Keywords: dept.lib

[Three Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Asymptote, 2012)
Keywords: dept.lib

[Two Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Absinthe: New European Writing, 2018)
Keywords: dept.lib; ⛔ No DOI found

[Six Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Metamorphoses: Journal of the Five-College Seminars on Literary Translation, 2013)
Keywords: dept.lib; ⛔ No DOI found

"Words" Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (One Sentence Poems, 2018)
Keywords: dept.lib

Heart Collector Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2015)
Finding murderers is just a day on the job for police captain Nadia Barka. But when a mutilated corpse is discovered in an old baptistery, she’s faced with some difficult questions: Who left a young woman’s body in a high-security museum in the middle of the night? And where is the victim’s heart?Barka has no leads, until several days later when unassuming computer technician Julien Lombard comes forward, claiming to have had a premonition of the woman’s abduction and murder. The ensuing investigation turns up nothing, however, and Julien is just as skeptical about his intel as the police are. But, after another woman goes missing, Barka decides to take a chance and trust in Julien’s gift. Does Julien hold the key to preventing another gruesome crime? Working together, can they find the murderer before he steals another heart?
Keywords: dept.lib; faculty_collection

Out of Sorts Translated by Wendeline Hardenberg - Valognes, Aurélie (Amazon Crossing, 2016)
Ferdinand Brun hasn’t always been a grumpy old man. Many years ago, he was a grumpy young man. Now he’d much rather spend time with his canine companion, Daisy, than any of his nosy neighbors. But as his behavior becomes increasingly peculiar, his daughter grows concerned and begins to consider moving him into a retirement home.In order to maintain his freedom, Ferdinand must submit to an apartment inspection by his longtime enemy, the iron-fisted concierge, Mrs. Suarez. Unfortunately, he’s never tidied up a day in his life. His neighbors, precocious ten-year-old Juliette and vivacious ninety-two-year-old Beatrice, come to the rescue. And once he lets these two into his life, things will never be the same. After an eighty-three-year reign of grouchiness, Ferdinand may finally learn that it’s never too late to start living.
Keywords: Aging; Fiction; Fiction; Families; Fiction; France; Fiction; Man-woman relationships; dept.lib; faculty_collection

Project Anastasis Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2016)
As a former soldier, private investigator Jean Legarec is used to high stakes and sharpshooters. But he doesn’t realize what he’s getting into when he agrees to investigate the disappearance of six-year-old Alexandre, the grandson of a highly influential French politician.For a million euros, Legarec launches a dangerous search that will dig deep into some of the darkest corners of European history. With the help of the boy’s beautiful aunt, Béatrice, he uncovers evidence of a modern-day terrorist plot rooted in a long-buried enterprise of the Third Reich. From Paris to Malta to the Vosges forest, a cast of witnesses—including a death camp survivor and former mercenaries—help Legarec piece together a terrifying truth.Yet even then, the PI worries that his own dark past and his undeniable attraction to Béatrice might be clouding the investigation. Can he put the personal aside in order to do his job? And can he free an innocent child from a web of absolute evil?
Keywords: dept.lib; faculty_collection

The Matrix and the Machine Translated by Wendeline Hardenberg - Ravalec, Vincent (Asymptote, 2018)
Keywords: dept.lib

Persephone 2014 Translated by Wendeline Hardenberg - Aubry, Gwenaëlle (Asymptote, 2019)
Keywords: dept.lib

Contemporary Art is Internationally Appealing by Vincent Ravalec, translated by Wendeline A. Hardenberg - Gaffey, Marlee (Tupelo Quarterly, 2018)
The challenge was to make appealing something that was not. To transform this godforsaken city, populated by people as indifferent to art as tourists are to the idea of visiting the only historic building—a vague ruin of a castle—in a glamorous destination. After all, what the Guggenheim did for Bilbao could be reproduced […]
Keywords: dept.lib

Twitter at the office - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2010)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/077-080-070-112-03X tex.type: [object Object]
Keywords: dept.lib

Subscriptions are us: content, access, & collections - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/137-350-398-102-179 tex.type: [object Object]
Keywords: dept.lib

Book Review: Latino america: how america's most dynamic population is poised to transform the politics of the nation - Dickens, Jeffrey I. (Library Journal, 2014)
tex.unique-id: ISI:000342482800169
Keywords: book.review; dept.lib; ⛔ No DOI found

Book Review: The meaning of human existence - Dickens, Jeffrey J. (Library Journal, 2014)
tex.unique-id: ISI:000342482800123
Keywords: book.review; dept.lib; ⛔ No DOI found

A theory of the drone. - Dickens, Jeffrey J. (Library Journal, 2015)
tex.unique-id: ISI:000347439900218
Keywords: dept.lib; ⛔ No DOI found

Give us the ballot: the modern struggle for voting rights in america - Dickens, Jeffrey J. (Library Journal, 2015)
tex.unique-id: ISI:000357845100220
Keywords: dept.lib; ⛔ No DOI found

Political animals: how our stone-age brain gets in the way of smart politics. - Dickens, Jeffrey J. (Library Journal, 2015)
tex.unique-id: ISI:000364113700190
Keywords: dept.lib; ⛔ No DOI found

And yet ... essays - Dickens, Jeffrey J. (Library Journal, 2016)
tex.unique-id: ISI:000367862900159
Keywords: dept.lib; ⛔ No DOI found

The politicians & the egalitarians: the hidden history of american politics - Dickens, Jeffrey J. (Library Journal, 2016)
tex.unique-id: ISI:000376228600231
Keywords: dept.lib; ⛔ No DOI found

The pragmatic superpower: winning the cold war in the middle east - Dickens, Jeffrey J. (Library Journal, 2016)
tex.unique-id: ISI:000371105400185
Keywords: dept.lib; ⛔ No DOI found

Tools of academic library assessment: the user survey - Liebst, Anne; Feinmark, David (Journal of Library Administration, 2016)
Academic libraries are taking a closer look at how well they are serving the needs of their users. As a result assessment activities become more important. In this column, the authors will focus on and describe one major tool of assessment—the user survey. © 2016, Published with license by Taylor & Francis.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-442-307-245-879 tex.type: [object Object]
Keywords: academic libraries; assessment; dept.lib; libraries—evaluation; library administration; library planning; user surveys

The breath of my life: constructing the self in chen ran’s A private life - Hardenberg, Wendeline A (Women's Studies, 2014)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-702-343-801-36X tex.type: [object Object]
Keywords: dept.lib

Review of collaboration in libraries and learning environments - Hedreen, Rebecca (Collaborative Librarianship, 2014)
Citation Key Alias: lens.org/082-774-764-581-129 tex.type: [object Object]
Keywords: dept.lib; ⛔ No DOI found

Time zones, screencasts, and becoming real: lessons learned as a distance librarian - Hedreen, Rebecca (Urban Library Journal, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-960-655-639-556 tex.type: [object Object]
Keywords: dept.lib

Building blocks for personal brands - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-002-113-520-877 tex.type: [object Object]
Keywords: dept.lib

Design for double rainbow - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/124-582-046-811-968 tex.type: [object Object]
Keywords: dept.lib

Google+ and the commodification of cool - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-170-969-515-573 tex.type: [object Object]
Keywords: dept.lib

Libraries, librarians and mobile services - Thomas, Lisa Carlucci (Bulletin of The American Society for Information Science and Technology, 2011)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-096-675-285-364 tex.type: [object Object]
Keywords: dept.lib

Gone mobile? - Thomas, Lisa Carlucci (Library Journal, 2010)
tex.unique-id: ISI:000283457000013
Keywords: dept.lib; ⛔ No DOI found

Library intranets: trends and enhancements - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/190-515-926-757-166 tex.type: [object Object]
Keywords: dept.lib

Service standards for the Mobile/Social library - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/125-177-835-426-699 tex.type: [object Object]
Keywords: dept.lib

Technical service outreach strategies for academic libraries - Toce, Jacqueline; Schofield, Cindy (Technical Services Quarterly, 2011)
The model of a library staff divided into technical and informational service divisions remains common-especially among academic libraries. The authors argue that in many ways it is now the technical services division that is best positioned to provide outreach services to a community-whether at the university or municipal level. Maintaining bibliographic access amid the changing information landscape hinges on a clear understanding of systems, metadata, and traditional organizational skills, all home grown in the back rooms of conventional libraries. The authors cite examples of library outreach that emanated from technical service departments and conclude that the sequestered staffs of the past must make themselves indispensible today by sharing their knowledge and talents, offering services to their communities that require their technical expertise, and advance the mission of the library organization. © Taylor & Francis Group, LLC.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-473-790-983-166 tex.type: [object Object]
Keywords: Academic libraries; Catalogers; Cooperative; Outreach; Service; Southern connecticut state university; Technical services; dept.ils; dept.lib

Will You Ever Change? Translated by Wendeline Hardenberg - Valognes, Aurélie (Amazon Crossing, 2017)
Charming, quirky, and funny, this oh-so-relatable novel from the bestselling author of Out of Sorts shines a light on the always-complicated je ne sais quoi of every family’s relationship.As Martine and Jacques Le Guennec prepare for their annual family Christmas dinner, Martine reminds her husband to be on his best behavior. Their son Nicolas is bringing his girlfriend, Jeanne, to their home for the first time, and she doesn’t want Jacques to scare this one off.Jacques has always ruled his roost with patriarchal bravado, and he can’t help but verbally antagonize everyone—especially the wives of his sons. Jeanne, a strong-willed woman who grew up without a father, clashes with the curmudgeon, and she worries that her boyfriend might be too much like his father.It’s all starting to make Martine question everything about her relationship with her husband. And, though she makes that perfectly clear to him, the old dog is not anxious to learn new tricks.When Jeanne saves Jacques’s life, he begins to realize it may be time to change his ways if he wants to hold on to his wife and keep the family close. But is it too late?
Keywords: dept.lib